Securing Decarbonisation and Growth. (November 2019) - Zenghelis, Dimitri
Executive Summary: The need to decarbonise the economy in order to slow the pace of climate change is now recognised as one of the most pressing international policy challenges. While the UK cannot by itself materially affect global climate change, it has an opportunity to play an influential role, both by persuading others of the need for action but also by reshaping its domestic economy to benefit from a low-carbon transition. Far from hampering competitiveness, adoption of a coordinated policy approach to climate change today would generate positive benefits for the UK economy, especially if it addresses the multiple market failures that promote pollution and places decarbonisation at the heart of structural economic policy. Desirable strategies would include public support for research, development, and deployment of new technologies, and measures to foster an environment where innovation can rapidly shift the economy from dirty to clean production systems. Focusing UK industrial strategy on securing strong domestic supply chains for green products and services, for example, could help create an early mover advantage in rapidly growing global market sectors. Interventions could include the establishment of a National Infrastructure Bank to support decarbonisation in crucial sectors such as energy and transport, and would also need to encompass measures to assist structural adjustment in affected industries and their workforces.